Sports and Marfan Syndrome - Salim, M. A.; Alpert, B. S. (The Physician and Sportsmedicine, 2001)
Marfan syndrome is an autosomal dominant disorder of the connective tissues. Its major manifestations are in the cardiovascular, musculoskeletal, and ocular systems. Recognizing the phenotypic presentation of tall stature, long limbs and fingers, chest deformity, myopia, midsystolic click, and systolic or diastolic murmur can lead to early diagnosis. Morbidity and mortality are primarily caused by cardiovascular involvement. The goal of medical therapy is to retard the aortic root dilation that leads to sudden death from dissection or rupture. Surgical interventions for mitral valve regurgitation and resection of aortic aneurysms are highly effective. In addition, individuals with Marfan syndrome should be restricted from participation in certain sports.